Decline of salt marsh-nesting birds within the lower Chesapeake Bay (1992–2021) - Bryan D. Watts (PLoS ONE, 2025)
Bird species that depend on tidal marshes throughout the world are threatened by ongoing sea-level rise. How species that differ in their level of marsh-dependency may respond to change over time remains unclear. I surveyed a network of patches (N = 186) within tidal salt marshes located in the lower Chesapeake Bay (1992, 2021) for 12 species of breeding birds to evaluate changes in abundance. Marsh-nesting bird abundance declined by 65.7% during the course of the survey interval. Significant declines in abundance were discovered for eight of ten species evaluated with declines in abundance ranging from 34 to 100%. Four species were extirpated or nearly extirpated within focal marshes during the study period. The magnitude of decline was highest for facultative nesting species (84.2%) followed by marsh obligates (81.6%) and salt marsh obligates (44.2%) respectively. Salt marsh obligates have become an increasingly dominant portion of the species assemblage over time reaching 83% of all detections by 2021. This pattern supports the prediction that specialists may persist longer than generalists as habitats are subjected to change. Despite their relative stability, salt marsh obligates are of high conservation concern over the longer term due to their specialization on a habitat that is currently experiencing rapid disruption. Even though this study did not evaluate the causes of population decline, results are aligned with other recent work within other regions that have implicated ongoing sea-level rise and nest predation.